ALDOSE REDUCTASE PROTECTS AGAINST EARLY ATHEROSCLEROTIC LESION FORMATION IN APO E - NULL MICE - Srivastava, Sanjay (2009)
RATIONALE: Atherosclerotic lesion formation is associated with the accumulation of oxidized lipids. Products of lipid oxidation, particularly aldehydes, stimulate cytokine production and enhance monocyte adhesion, however their contribution to atherosclerotic lesion formation remains unclear. OBJECTIVE: To test the hypothesis that inhibition of aldehyde removal by aldose reductase (AR), which metabolizes both free and phospholipid aldehydes, would exacerbate atherosclerotic lesion formation. METHODS AND RESULTS: In atherosclerotic lesions of apoE-null mice, AR protein was localized with macrophage-rich regions and its abundance increased with lesion progression. Treatment of apoE-null mice with AR inhibitors sorbinil or tolrestat increased early lesion formation, but did not affect the formation of advanced lesions. Early lesions of AR(−/−)/apoE(−/−) mice maintained on high fat diet were significantly larger when compared with age-matched AR(+/+)/apoE(−/−) mice. The increase in lesion area due to deletion of the AR gene was seen in both male and female mice. Pharmacological inhibition or genetic ablation of AR also increased the lesion formation in male mice made diabetic by streptozotocin treatment. Lesions in AR(−/−)/apoE(−/−) mice exhibited increased collagen and macrophage content and a decrease in smooth muscle cells. AR(−/−)/apoE(−/−) mice displayed a greater accumulation of the AR substrate 4-hydroxy trans-2-nonenal (HNE) in the plasma and protein-HNE adducts in arterial lesions than AR(+/+)/apoE(−/−) mice. CONCLUSIONS: These observations indicate that AR is upregulated in atherosclerotic lesions and it protects against early stages of atherogenesis by removing toxic aldehydes generated in oxidized lipids.